The impact of new information technology in Africa - Alemna, A.A. (Information development, 1999)
Stresses the importance of New Information and Communication Technologies in Africa. Provides an analysis of the opportunities and challenges facing African countries in their attempt to introduce and implement policies meant to encourage the use of these technologies. Concludes that although African countries in general acknowledge the importance of the information revolution, very little concrete action has been taken in this area.